Hormonal Regulators of Appetite. (20th November 2008) - Austin, Juliana; Marks, Daniel
Abstract : Obesity is a significant cause of morbidity and mortality worldwide. There has been a significant worsening of the obesity epidemic mainly due to alterations in dietary intake and energy expenditure. Alternatively, cachexia, or pathologic weight loss, is a significant problem for individuals with chronic disease. Despite their obvious differences, both processes involve hormones that regulate appetite. These hormones act on specific centers in the brain that affect the sensations of hunger and satiety. Mutations in these hormones or their receptors can cause substantial pathology leading to obesity or anorexia. Identification of individuals with specific genetic mutations may ultimately lead to more appropriate therapies targeted at the underlying disease process. Thus far, these hormones have mainly been studied in adults and animal models. This article is aimed at reviewing the hormones involved in hunger and satiety, with a focus on pediatrics.